Cobalt mediated electro-scrubbers for the degradation of gaseous perchloroethylene. (September 2021) - Escalona-Durán, F.; Muñoz-Morales, M.; Souza, F.L.; Sáez, C.; Cañizares, P.; Martínez-Huitle, C.A.; Rodrigo, M.A.
Abstract: This work focuses on the treatment of gaseous perchloroethylene (PCE) using electro-scrubbing with diamond electrodes and cobalt mediators. PCE was obtained by direct desorption from an aqueous solution containing 150 mg L −1, trying to a real pollution case. The electro-scrubber consisted of a packed absorption column connected with an undivided electrochemical cell. Diamond anodes supported on two different substrates (tantalum and silicon) were used and the results indicated that Ta/BDD was more successful in the production of Co (III) species and in the degradation of PCE. Three experimental systems were studied for comparison purposes: absorbent free of Co (III) precursors, absorbent containing Co (III) precursors, and absorbent containing Co (III) precursors undergoing previous electrolysis to the electro-scrubbing to facilitate the accumulation of oxidants. The most successful option was the last, confirming the important role of mediated electrochemical processes in the degradation of PCE. Trichloroacetic acid (TCA) and carbon tetrachloride (CCl4 ) were found as the primary reaction products and ethyl chloroacetate esters were also identified. A comprehensive mechanism of the processes happening inside electro-scrubber is proposed. Graphical abstract: Image 1 Highlights: Ta/BDD promoted higher conversion of Co(III) reaching 90% after 2 h. Si/BDD electrolysis attained 75.7% while Ta/BDD reached 90.5% of PCE removal. Mediated electrooxidation with Co improved the PCE degradation rate. Electrolysis with Si/BDD anode favors the generation of TCA as by-product.